Effect of agroecological zones and planting condition on plant height and yield in forage oats in the Puno region, Perú - Zeballos-Caban, Julio Cesar (2022)
The present study of A. sativa golden variety cayuse, was carried out in six communities of dry puna (PS) and six communities of wet puna (PH) in the Puno region. The objectives were to evaluate the influence of two agroecological zones PS and PH, two planting conditions in roosts (D) and breaking ground (TR), on the plant height (cm) and yield (kg/MS/ha) in addition to determine the best combination. A metric ruler was used to estimate the plant height and the quadrant method was used for the yield, the DECA with two factors was used, the data analysis was performed in the SAS statistical program version 9.4. According to the analysis of variance and Tukey’s test, for the main effects by agroecological zone, the plant height in PH and PS was 41 and 21 cm in length respectively (p> 0.05), in yield 6551 and 1623 were obtained kg/MS/ha (p <0.05); according to the sowing condition, the plant height in D and TR was 39 and 23 cm respectively (p> 0.05), in yield it was obtained 5394 and 2779 kg/MS/ha (p> 0.05); for simple effects in combinations, PHD, PHTR, PSD and PSTR, the plant height was 50, 31, 28 and 14 cm in length respectively (p> 0.05), in yield 8917, 4185, 1872 and 1374 were obtained kg/MS/ha respectively (p <0.05). It is concluded that the agroecological zone has a significant influence on yield and the best significant combination for yield is PH*D.